2023
DOI: 10.1101/2023.01.10.523453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and Applications of Evoked Responses During Epidural Electrical Stimulation

Abstract: Epidural electrical stimulation (EES) of the spinal cord has been FDA approved and used therapeutically for decades. However, there is still not a clear understanding of the local neural substrates and consequently the mechanism of action responsible for the therapeutic effects. Epidural spinal recordings (ESR) are collected from the electrodes placed in the epidural space. ESR contains multi-modality signal components such as the evoked neural response (due to tonic or BurstDR waveforms), evoked muscle respon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recently, some research work also indicated that the recorded evoked responses from the non-stimulation contacts during SCS could contain electromyography (EMG) signals from nearby muscle contractions as well as ECAPs (7). Therefore, the epidural spinal recordings (ESR) are collected from electrodes placed in the epidural space and contain multi-modality signal components such as the ECAP, the evoked muscle response, stimulation artifacts, and cardiac response (8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some research work also indicated that the recorded evoked responses from the non-stimulation contacts during SCS could contain electromyography (EMG) signals from nearby muscle contractions as well as ECAPs (7). Therefore, the epidural spinal recordings (ESR) are collected from electrodes placed in the epidural space and contain multi-modality signal components such as the ECAP, the evoked muscle response, stimulation artifacts, and cardiac response (8).…”
Section: Introductionmentioning
confidence: 99%